Caribbean Community : facing the challenges of regional and global integration - Jessen, Anneke (INTAL-IDB Buenos AiresAR, 1999)
Tries to answwer questions on CARICOM such as: How it arrived there? How can it move on? and What role integration plays in these developments? Does this by examining CARICOM's past achievements, identifying key obstacles to its successful regional and global integration and suggesting practical solutions to overcoming these obstacles . Focuses mainly on economic issues.